Strategi Kepala Tata Usaha dalam Meningkatkan Kepuasan Layanan Administrasi Pendidikan - M Fikri Maula Syafeii; Ilham Fahmi; Nur Rochimah (Al-Abshar: Journal of Islamic Education Management, 2026)
Problem: Despite growing research on educational administrative service quality, there is limited study examining the leadership strategies of heads of administration (kepala tata usaha) in state Islamic secondary schools (Madrasah Aliyah Negeri) in the context of digital transformation in Indonesia. Purpose: This study aims to analyze the strategies employed by the head of administration at MAN 2 Karawang in improving educational administrative service satisfaction, through the lens of SERVQUAL dimensions. Method: A descriptive qualitative approach was used, involving seven purposively selected informants: the school principal, head of administration, one administrative staff, two teachers, and two students. Data were collected through semi-structured interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model (data reduction, data display, and conclusion drawing/verification), with triangulation for validity. Results: Four interlocking strategies were identified: (1) enforcing work discipline tied to staff competency mapping; (2) strengthening interpersonal communication and team coordination; (3) integrating digital administrative technology into service workflows; and (4) implementing structured weekly supervision and evaluation cycles. These strategies produced measurable improvements in service responsiveness, reliability, and user satisfaction as perceived by students and teachers. Contribution: This study offers an integrated strategy model for madrasah administrative leadership in the digital era, contributing novel theoretical and practical insights to Islamic educational management literature beyond previously reported isolated findings.